PERKEMBANGAN PONDASI TIANG KAYU PADA RUMAH TINGGAL DI BANJARMASIN - Nurfansyah, Nurfansyah; Saud, Muhammad Ibnu; Wastuti, Prima Widya; Aini, Ahmad Qurrata; Agusniansyah, Nursyarif (INFO-TEKNIK, 2020)
Banjarese houses are developed especially in the wooden foundation’s construction. In case, this construction had many problems as an unstable foundation that caused building slope, building renovation, vertical development, etc. Pole stick hardwood timbers are needed to strengthen to support the building’s load. Based on this condition, it is necessary to conduct research related to find a model that explained how wooden foundations are modified. This paper's method was to collect field observation data by a photograph. Samples of observation were chosen that show the modification and variation progress of pole stick hardwood and woodpile foundation. Applied modification models were founded, that it were combined the wooden foundations with concrete foundations. It is useful to strengthen the building’s load support. This model was suited to the wetland area.